Single and Attractive: Uniqueness and Stability of Economic Equilibria Under Monotonicity Assumptions - Patrizio Bifulco; Jochen Glück; Oliver Krebs; Bohdan Kukharskyy (CESifo GmbH, 2025)
This paper characterizes equilibrium properties of a broad class of economic models that al-low multiple heterogeneous agents to interact in heterogeneous manners across several markets. Our key contribution is a new theorem providing sufficient conditions for uniqueness and stability of equilibria in this class of models. To illustrate the applicability of our theorem, we characterize the general equilibrium properties of two commonly used quantitative trade models. Specifically, our analysis provides a first proof of uniqueness and stability of the equilibrium in multi-country trade models featuring (i) multiple sectors, or (ii) heterogeneity across countries in terms of their labor cost shares. These examples also provide a practical toolkit for future research on how our theorem can be applied to establish uniqueness and stability of equilibria in a broad set of economic models.
Keywords: D50; C62; F11; R13; 330; uniqueness; stability; general equilibrium; quantitative trade; networks